IHSAN (Islamic Healing & Self-Awareness Narrative): An Islamic Expressive Writing Model for Strengthening Emotional Regulation in Madrasah Adolescents - Eka Chandra Oktaviani; Ahmad Sarbini; Nani Nuranisah Djamal; Taufiq Hidayat (Program Studi Bimbingan dan Konseling Islam, 2026)
his study developed and evaluated the IHSAN (Islamic Healing & Self-Awareness Narrative) model as a structured Qur’anic reflection–based expressive writing intervention to enhance emotion regulation among madrasah adolescents. Using a modified Research and Development design, the model was validated by experts and implemented in an eight-week program involving 92 Grade XI students at MAN 1 Sumedang. Emotion regulation was measured using the Difficulties in Emotion Regulation Scale (DERS) and the Emotion Regulation Questionnaire (ERQ) (α > .87). Paired-samples t-tests indicated a significant reduction in overall emotion regulation difficulties (p < .001, d = 0.87) and a significant increase in cognitive reappraisal (d = 0.79). Implementation feasibility was rated very high (M = 4.71–4.75). The findings demonstrate that tafakkur, emotion labeling, and structured reflective writing can be operationalized as systematic psychopedagogical mechanisms integrating Islamic spiritual reflection within an antecedent-focused emotion regulation framework. The study contributes theoretically by extending emotion regulation theory into a religio-spiritual context and practically by providing a validated, scalable intervention model for madrasah-based guidance and counseling services.